Rare Coexistence of Acute Monoblastic Leukemia with Chronic Lymphocytic Leukemia - Bhar, Vikrant Singh; Gupta, Vasudha; Sharma, Mahak; Dhawan, Rishi; Modi, Shilpi; Vijyaran, Mona (Case Reports in Hematology, 2018)
Acute monoblastic leukemia (AMoL) is a rare hematopoietic neoplasm, and simultaneous occurrence of acute monoblastic leukemia with chronic lymphocytic leukemia is very rare and only a few cases have been reported in the literature. We here report a rare case of dual hematological malignancy in an 85-year-old male. The peripheral blood and bone marrow examination revealed dual population of atypical cells, comprising large cells with opened-up chromatin having monocytic appearance and small mature-appearing lymphocytes. Flowcytometric immunophenotyping confirmed the monocytic lineage of cells, whereas small lymphocytes showed the immunophenotype consistent with chronic lymphocytic leukemia (CLL). The final diagnosis was made as acute monoblastic leukemia with associated CLL. This is a rare case scenario, and this highlights the importance of careful morphological examination and flowcytometric immunophenotyping in the exact characterization of hematopoietic malignancies.